Fatigue life evaluation of deck to U-rib welds in orthotropic steel deck integrating weldment size effects on welding residual stress. (June 2021) - Jiang, Fei; Fu, Zhongqiu; Ji, Bohai; Wan, Lv
Highlights: The concept of weldment size effect on welding residual stresses (WRSs) in orthotropic steel decks was first outlined. A flow for the analysis of the weldment size effect was established based on three proposed hypotheses. The weldment size effect was investigated with a case study, including the longitudinal and transverse size effects. Fatigue life evaluation integrated with the weldment size effect on WRSs was performed for the deck to U-rib welds. Abstract: Fatigue of orthotropic steel decks (OSDs) has significantly limited the service life of such structures, and the welding residual stress (WRS) has been reported as a prominent factor that should be considered in their fatigue life evaluations. However, the weldment size effect on WRSs is often neglected in the conventional evaluation. This paper performed fatigue life evaluations of deck to U-rib welds in an OSD integrating the weldment size effects. First, the concept and hypotheses of the weldment size effect on WRSs were outlined in detail. Second, the sequential coupling method was selected for the WRS simulation, which was then experimentally verified using the blind hole method. Third, the influences of longitudinal and transverse weldment sizes on WRSs were analyzed by comparing the simulated WRS results corresponding to welding structures with different longitudinal sizes and U-rib numbers, respectively. Finally, fatigue life evaluation of the welds was conducted based on a modified S-N curve. The results show that (1) the WRSs at the welds can be accurately simulated through the adopted thermal-structural sequential coupling method; (2) the weldment size has a definite influence on the local distribution of WRSs: the WRS decreases exponentially with the increase of the longitudinal welding length; (3) the proposed method, which integrates the size effect on WRSs with the life evaluation, provides a relatively reasonable fatigue life for the deck to U-rib welds. In summary, the findings of this study enhance our understanding of the distribution laws of WRSs in OSDs, and suggest that it is vital to integrate the weldment size effects on WRSs in the process of accurately predicting fatigue life.